Media “Audio Visual” untuk Pembelajaran Kemahiran Menulis (Imla’) - Ela Isnani Munawwaroh (Universitas Ahmad Dahlan, 2021)
Abstract: The ability of students in Islamic universities to write Arabic correctly is very important. Therefore, it is very important to have learning related to tahsinul kitabah or improving Arabic writing. The problem that the writer finds in the process of learning tahsinul kitabah is that there are still many students who have very low writing skills in Arabic. This is partly due to the previous educational background. For this reason, a learning innovation is needed that can help students improve their writing skills even for those who do not have an educational background in previous Islamic religious schools. This paper contains a study of several learning media theories which are mixed in a learning media design. The results of this study, the authors produced an audiovisual learning media for imla 'learning, namely silent audio-visual media, in the form of books / sheets and sound (audio).